MARK WATNEY’S STRUGGLE TO LIVE ON MARS IN ANDY WEIR’S THE MARTIAN - Ridwan Saputra; Anik Cahyaning Rahayu; Sudarwati Sudarwati (Universitas 17 Agustus 1945 Surabaya, 2023)
Human beings have various needs in their life that must be fulfilled wherever they live. They must struggle to fulfill or satisfy their needs. Relating to this problem, this article deals with Mark Watney’s struggle to live on Mars seen in Andy Weir’s The Martian. This article describes the analysis of Mark Watney’s struggle while he gets stuck on Mars by fulfilling his needs. In doing the research, the descriptive qualitative method is used to remain focused on the data and interpretation. The data source of the research is the novel entitled The Martian written by Andy Weir. Abraham Maslow's theory of hierarchy of needs is used to analyze Mark Watney’s needs and his struggle to fulfill his needs. As a result, it is found that Mark Watney has all five stages of Abraham Maslow's Hierarchy of Needs and he struggles to fulfill each of these needs one by one. The followings show the result of the research. The physiological needs Watney has is mainly needs of food because he has a shortage of food. Watney struggles hard to fulfill his needs with the available supplies by going on a diet. The second is safety needs, Watney feels unsafe because on Mars, to overcome this need, Watney struggles to try to contact the crews on Earth. The third need is love and belongings needs. Living alone on Mars without love from friends and family and he is considered dead makes him depressed. The fulfillment of the needs relates to the finding of the pathfinders which enables him to communicate with the crew of NASA. He no longer feels lonely and depressed and then feels happy. The fourth one is Esteem Needs. He becomes proud of himself knowing that he is highly appreciated and valued as a hero to the team since he is the only one who masters all the engineering parts of the mission. The last one is self-actualization needs. Watney must struggle to survive, which shows the fulfillment of his need. In conclusion, Mark Watney’s struggle finally can make him fulfill all his five needs on Mars and land on Earth safely.